2013
DOI: 10.1785/0120120197
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Ground Motion from Induced Earthquakes in Geothermal Areas

Abstract: Induced seismicity from anthropogenic sources can be a significant nuisance to a local population and in extreme cases lead to damage to vulnerable structures. One type of induced seismicity of particular recent concern, which, in some cases, can limit development of a potentially important clean energy source, is that associated with geothermal power production. A key requirement for the accurate assessment of seismic hazard (and risk) is a ground-motion prediction equation (GMPE) that predicts the level of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 65 publications
(88 reference statements)
3
99
0
Order By: Relevance
“…Moreover, in keeping with traditional response spectral GMPEs, the empirical FAS model of Bora et al (2014) also used only M w , R JB , and V S30 as the predictor variables. Importantly, the aleatory variability in the response spectral amplitudes obtained through our initial approach was also significantly larger than those of other GMPEs developed under the same project, with the exception of the model of Bindi et al (2014), as depicted in figure 9 of Douglas et al (2014).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, in keeping with traditional response spectral GMPEs, the empirical FAS model of Bora et al (2014) also used only M w , R JB , and V S30 as the predictor variables. Importantly, the aleatory variability in the response spectral amplitudes obtained through our initial approach was also significantly larger than those of other GMPEs developed under the same project, with the exception of the model of Bindi et al (2014), as depicted in figure 9 of Douglas et al (2014).…”
Section: Introductionmentioning
confidence: 79%
“…Only the GMPEs of Akkar, Sandık-kaya, and Bommer (2014), Bindi et al (2014), andBora et al (2014) are considered for comparison, because they involve a parametric functional form in their regression analysis. Comparison among the median GMPEs was performed for the same scenarios of magnitude, distance, and V S30 , which have been used in Douglas et al (2014). It is worth noting that Douglas et al (2014) uses the comparison paper of Abrahamson et al (2008) as a template; hence a comparison between the figures presented here can also be made to those shown in Abrahamson et al (2008) and the recently published Next Generation Attenuation-West 2 (NGA-West 2) models of Gregor et al (2014).…”
Section: Response Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the within-event standard deviation of the GMPE was much larger than that the data exhibited. This was noted by the authors as a result of combining data from various datasets, with lower uncertainty evident if analysing data from specific regions [55]. The target for the simulations was to reproduce the ground-motion field of the M = 3.2 event (Figure 2).…”
Section: Datamentioning
confidence: 95%
“…Here we focussed on PGV, which is useful as it is a measure of ground motion on which Swiss norms for vibration disturbances are based. The GMPE of Douglas et al [55] is also shown in Figure 2. The GMPE performance is good at distances of interest for induced seismicity, (e.g., R < 30 km), with PGV values falling within the model's (large) standard deviation.…”
Section: Datamentioning
confidence: 98%